Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1136/bmjdrc-2021-002746
|View full text |Cite
|
Sign up to set email alerts
|

Plasma C1q/tumor necrosis factor-related protein-3 concentrations are associated with diabetic peripheral neuropathy

Abstract: IntroductionTo analyze the associations of circulating C1q/tumor necrosis factor-related protein-3 (CTRP3) concentrations with several metabolic parameters and to investigate the possible role of CTRP3 in subjects with diabetic peripheral neuropathy (DPN).Research design and methodsA total of 347 participants were recruited in this study, and plasma CTRP3 concentrations were analyzed in subjects with DPN (n=172) and without DPN (non-DPN, n=175). The nerve conduction test and oral glucose tolerance test were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…To induce sepsis, mice were injected with 30 mg/kg LPS. Results showed that CTRP6 was downregulated in lungs peripheral neuropathy, 19 while CTRP6 deficiency enhanced complement activation and contributed to development of inflammatory diseases. 14 This study found that CTRP6 exhibited anti-inflammatory effect to protect against sepsisassociated lung injury and inhibited neutrophil extracellular traps formation.…”
Section: Ctrp6 Ameliorated Septic Lung Injurymentioning
confidence: 99%
“…To induce sepsis, mice were injected with 30 mg/kg LPS. Results showed that CTRP6 was downregulated in lungs peripheral neuropathy, 19 while CTRP6 deficiency enhanced complement activation and contributed to development of inflammatory diseases. 14 This study found that CTRP6 exhibited anti-inflammatory effect to protect against sepsisassociated lung injury and inhibited neutrophil extracellular traps formation.…”
Section: Ctrp6 Ameliorated Septic Lung Injurymentioning
confidence: 99%